The public health challenges of female migration: the Venezuelan diaspora in Andean countries - Sarahí Rueda-Salazar; Jenny García (BMC, 2024)
Abstract Background Venezuelan migration has experienced an unprecedented increase in the last decade, with approximately 7.7 million Venezuelan-born individuals residing in other countries as of 2024. Our study aims to identify the potential and actual demand for healthcare services (SRH) in the Venezuelan diaspora's four primary destinations within the Andean Countries: Colombia, Ecuador, Peru, and Chile. Methods Using official data from administrative records, censuses, and sample surveys reported by the host countries and international agencies, we estimate the annual evolution of Venezuelan-born women of reproductive age (WRA) and their offspring. Additionally, we conduct two case studies focusing on Colombia and Chile to analyse the groups most vulnerable to unmet health needs. Results The population of WRA has increased to between 5 and 6.8%, and births have risen to approximately 3-8% in host countries due to Venezuelan migration. Yet, we found a general decrease in health coverage for certain age groups of Venezuelan female migrants in host countries for the period 2017-2022, particularly in Chile. By 2022, an estimated 20% of healthcare needs remained unmet among children, girls, and younger Venezuelan women, contributing to greater health inequalities between Venezuelan-born adolescents and those from other countries of birth. Conclusions Our findings highlight the escalating demand for and limited access to healthcare services among Venezuelan WRA in their destinations. Unmet healthcare needs are particularly prevalent among younger women by 2022, underscoring the urgency for health system to incorporate gender-responsive, equitable interventions and ensuring health rights for high-risk migrant groups such as infants, children, adolescents, and younger women. Addressing these challenges remains a critical task for the regional public health agenda in Latin America.